Fenomena Sosial Pengemis Anak di Kota Banda Aceh - Ismi, Dirsya (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
The begging phenomenon is considered a social problem that must be resolved immediately, so that its negative impacts can be minimized from an early age. The government has made various efforts to curb child begging, both in the form of training and ways to prevent child beggars from being active on the streets, but these have not gone well. The aim of this research is to find out how children beggars live and children's activities in begging in Banda Aceh City. The research approach and method used in this research is a qualitative approach and a method that uses qualitative descriptive methods. The data collection techniques used in this research are observation, interviews and documentation. The research results show that the large number of child beggars in Banda Aceh City is due to encouragement from parents and invitations from other people with the lure of getting money and that the child beggars in Banda Aceh City are mostly outsiders who live in Banda Aceh and Aceh Besar. Some of them no longer go to school because they prefer to beg and decide to become beggars due to economic factors. The way they beg is by wearing a cap, sarong and charity box. The income they get when begging is Rp. 90,000 to Rp. 120,000 so they decided not to go to school anymore and preferred to beg.